PENGARUH PENERAPAN MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) TERHADAP HASIL BELAJAR EKONOMI PESERTA DIDIK KELAS XI - Oktavia, Intan; Jaya, Wayan Satria; Arga, Kharisma Idola (LPPM STKIP PGRI Bandar Lampung, 2020)
The problems in this study are 1) the low student learning outcomes, 2) the lack of student activity in the teaching and learning process, 3) and the CIRC learning model in the classroom has never been applied. The purpose of this study was to determine the effect of the application of the Cooperative Integrated Reading and Composition (CIRC) learning model on the economic learning outcomes of XI graders in the even semester of Gedongtataan 1 Public High School 2018/2019. The method used in this study is the experimental method. The population in this study were all students of class XI.IPS 1 Gedongtataan High School totaling 94 students, the sample consisted of two classes namely class XI IPS 2 and XI IPS 3, where class XI IPS 2 as an experimental class which amounted to 33 students and class XI IPS 3 as a control class with 33 students. The sampling technique uses cluster random sampling technique. The instrument in this study used multiple choice tests and hypothesis testing in this study using the formula ttes. Hypothesis testing using the statistical formula t-test obtained t hit = 6.22 and the distribution table t at a significant level of 5% is known tdaf is t (1-1 / 2 Î±) = 2.00 so that it is proven thit> t daf. Thus it can be concluded that